Electromoxibustion for knee osteoarthritis in older adults: A pilot randomized controlled trial. (November 2020) - Cheung, Teris; Ho, Yuen Shan; Yuen, Chun-Sum; Lam, Chun-Sing; Chun-Lung So, Billy; Chen, Shu-Cheng; Leung, Doris Y.P.; Kwai-Ping Suen, Lorna; Tin-Yau So, Larry; Chun-Hei Ho, Alex; Yeung, Wing-Fai
Abstract: Background: Electromoxibustion devices are commercially available and can be self-administered by patients. Nevertheless, little is known about the effectiveness and potential burn injury of these devices as this topic is under-investigated. Objective: To assess the preliminary effects and safety of an electromoxibustion (EM) device for improving knee pain and joint functions in older adults with knee osteoarthritis (KOA). Design, setting, participants and intervention: This was a pilot two-armed assessor-blinded randomized controlled trial to assess the effects of electromoxibustion (EM) on older adults with KOA. A total of 38 subjects aged 60 or above, with KOA for 3 months or above were recruited. Participants were randomized to the EM group or the knee health education group. The intervention group (n = 21) received 12 sessions of EM spanning across four weeks, while the control group (n = 17) received two sessions of knee health education. Main outcome measures: Primary outcome included the pain severity Numerical Rating Scale (NRS) at baseline and week 4. Secondary outcomes included the Western Ontario and McMaster University Osteoarthritis Index (WOMAC), Short-Form Six-Dimension (SF6D), Timed Up & Go Test (TUG) and Fast Speed Gait (FSG). Results: Both groups showed a decreasing trend in knee pain intensity by NRS at post-intervention. There were also trends of improvement in the WOMAC score, TUG score, FGS test score and SF-6D score at week 4. Only a small between-group effect size (d = 0.13) was found, but medium between-group effects sizes were found in the WOMAC total score (d = 0.40) and WOMAC functional sub-score (d = 0.51). However, the differences were not statistically significant. Conclusion: This study suggested that EM may be beneficial for KOA in older adults, particularly in terms of improving knee function. Replication of similar studies in larger RCTs is warranted to confirm the effectiveness of EM on reducing pain and knee function of older adults with KOA. Trail registration number: NCT04034394. Highlights: Both electromoxibustion and knee health education showed a decreasing trend in knee pain intensity. Electromoxibustion is beneficial for KOA in older adults, particularly in terms of improving knee function. Larger RCTs are warranted to confirm the effectiveness of EM on reducing pain and knee function of older adults with KOA.